Rumah Qur’an Itqonul Iman Sebagai Wadah Dalam Meningkatkan Budaya Literasi Baca Al-Qur’an Anak-anak Di Desa Mislak - Nabila, Pinka; Ramadhina, Ghina; Hikmah, Karimatul; Hafizah, Nur; Sari, Mitha (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
The Al-Qur'an literacy program is an activity that supports students' ability to develop a culture of reading the AlQur'an. The focus of the problem discussed is how effective Al's literacy activities are The Qur'an has an impact on students in reading the Qur'an. This research aims to find out how the Al-Qur'an literacy activities process and find out the effectiveness of Al-Qur'an literacy activities in having an impact on students in reading the Al-Qur'an. This type of research is descriptive research with a qualitative approach. The data sources for this research are primary data, namely the results of interviews with informants and secondary data, namely data obtained from observation notes, books and journalsThis research shows that Al-Qur'an literacy activities start from the stage of determining the schedule for Al-Qur'an literacy activities, the time and place for carrying out Al-Qur'an literacy activities and those involved in Al-Qur'an literacy activities. As for form the form of Al-Qur'an literacy activities includes a series of AlQur'an literacy activities, methods of implementing Al-Qur'an reading and materials and assessments on Al-Qur'an literacy activities Qur'an. Al-Qur'an literacy activities have a good impact on students. The results of Al-Qur'an literacy activities for students are that Al-Qur'an literacy activities can increase students' interest in reading the AlQur'an, Al-Qur'an literacy activities provide motivation for students in cultivating reading the Al-Qur'an and Al-Qur'an literacy activities provide moral education to students through the verses they read.